Comparison of continuous sampling with active noise cancelation and sparse sampling for cortical and subcortical auditory functional MRI. Issue 5 (1st July 2021) - Dewey, Rebecca S.; Hall, Deborah A.; Plack, Christopher J.; Francis, Susan T.
Abstract : Purpose: Detecting sound‐related activity using functional MRI requires the auditory stimulus to be more salient than the intense background scanner acoustic noise. Various strategies can reduce the impact of scanner acoustic noise, including "sparse" temporal sampling with single/clustered acquisitions providing intervals without any background scanner acoustic noise, or active noise cancelation (ANC) during "continuous" temporal sampling, which generates an acoustic signal that adds destructively to the scanner acoustic noise, substantially reducing the acoustic energy at the participant's eardrum. Furthermore, multiband functional MRI allows multiple slices to be collected simultaneously, thereby reducing scanner acoustic noise in a given sampling period. Methods: Isotropic multiband functional MRI (1.5 mm) with sparse sampling (effective TR = 9000 ms, acquisition duration = 1962 ms) and continuous sampling (TR = 2000 ms) with ANC were compared in 15 normally hearing participants. A sustained broadband noise stimulus was presented to drive activation of both sustained and transient auditory responses within subcortical and cortical auditory regions. Results: Robust broadband noise‐related activity was detected throughout the auditory pathways. Continuous sampling with ANC was found to give a statistically significant advantage over sparse sampling for the detection of the transient (onset) stimulus responses, particularly in the auditory cortex ( P < .001) and inferior colliculus ( P < .001), whereas gains provided by sparse over continuous ANC for detecting offset and sustained responses were marginal ( p 0.05 in superior olivary complex, inferior colliculus, medial geniculate body, and auditory cortex). Conclusions: Sparse and continuous ANC multiband functional MRI protocols provide differing advantages for observing the transient (onset and offset) and sustained stimulus responses.